Repentance Creek [large type] - Cole, Tobias (Sharpshooter, 2020)
"Former Union Army sharpshooter Jed Wells had vowed to give up killing after the war ended. Even after the last shot was fired, he continued to carry his hated sharpshooter's rifle as a grim reminder of what he once was. But while on a trip to a remote cattle town, his stagecoach is robbed, a man is killed, and his rifle is stolen. With the help of a hard-hitting cowboy named Charlie Crowder, Jed sets out to hunt down the two masked men responsible and recover his lost property. But the trail is leading them into the strange and troubled lives of a wealthy and powerful family, and toward an unexpected confrontation in the small Texas town of Repentance Creek, where it seems everyone -- including a beautiful and mystifying young woman -- guards a deadly secret"--